The Effect of Different Carbohydrates and Amino Acids on the Activity of Selected Antimicrobial Compounds against Mycobacterium Smegmatis - Debrah, M.A. (University of Ghana, 2021)
Antibiotics play a significant role in the medical treatment of bacterial diseases. Bacteria respond to antibiotic stress by several means including the initiation of stress responses that promote recruitment of resistance determinants or physiological changes that compromise antimicrobial activity. The overdependence and misuse of these drugs have led to the emergence of resistance in microorganisms which complicates patient management and as such, different strategies are being sought to alleviate this threat that such resistant pathogens pose. One such strategy is chemo sensitization where compounds are used to potentiate the effect of antibiotics. This study investigates the effect of selected carbohydrates and amino acids on the efficacy of antimicrobial across different classes, against Mycobacterium smegmatis strains to provide insight into key cellular processes associated with the functioning of antibiotics, and whose modulation would be key in sustaining antibiotic action and preventing resistance development. Seventeen (17) compounds across fifty-three (53) triple-combinations were screened in an experimental set-up from which 29 combinations were identified that robustly break resistance and 24 that robustly induce resistance. The top two (2) conditions that break resistance (SOR (3X) and MAL (3X)) led to the activation of fifteen (15) antibiotics and the top two (2) that induce resistance (LAC (3X) and SIA+ADO (1.5X)) led to the loss of efficacy of twelve (12) antibiotics. The top two (2) compounds in each category (resistance breaking & resistance inducing) were then prioritized for gene expression analysis looking at a landscape of stress response regulons in both Mycobacterium smegmatis (wt) and multidrug-resistant strains. The resistant breaking compounds induced genes such as vapC that’s responsible for toxicity in the organism, which correlates with its resistant breaking property but also the expression of virulence genes, that is lsr is in contrast.
MPhil. Molecular Biology
Keywords: Bacteria; antibiotic stress; medical treatment